Sustainability Literacy: What is its Impact on Pro-Environmental Behavior and Students' Ecological Competence? - Tria Mubarokah; Wirawan Fadly; Sam Ol Kong (Journal of Natural Science and Integration, 2026)
The urgent need for environmental preservation requires a fundamental shift in human behavior, which can be achieved through education focused on sustainable development. This study is aimed at analyzing the effect of understanding the concept of sustainable development on pro-environmental behavior and ecological competence among students at MA Al-Islam Joresan. This research employed a quantitative approach with a causal-associative design. Data were gathered through standardized test instruments and structured questionnaires. The target population comprised 11th-grade science students, from which the sample was drawn in two distinct phases. Initially, 23 students participated in a preliminary assessment, followed by the selection of the 20 highest-scoring individuals for the subsequent questionnaire phase. Purposive sampling was utilized based on practical constraints of time and accessibility, ensuring that participants' age, cognitive level, and existing knowledge were aligned with the research objectives. Data analysis used descriptive statistics to identify low scores and the Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach for inferential testing.The PLS-SEM analysis indicates that conceptual understanding has a significant positive effect on pro-environmental behavior (R² = 0.780) and ecological competence (R² = 0.646). These findings demonstrate that strengthening cognitive literacy fosters concrete environmental action in schools. The implication is that educational institutions should reposition their curricula by integrating digital technology to transform students into agents of environmental change. Keywords: ecological competence, sustainable development, pro-environmental behavior, PLS-SEM